(3eLehY abgis - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s ((3XGgQ OeTb s)
(3ChdgG (B:s
(3eMd GSJNGQI ai aQYjf ef GdELGQI s
(3BNQgG (B:s
(3ef CbSWh Gh ef ZdhG ai Mce ef jbhd (B: (3dh s
(3GdfSNI HgG MhGTs
(3jMJhi gPG GdeLehY Ydi YOI QSGFds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
Keywords: (3Gdabg GdTGaYjs